Transscleral tunnel incision related arterial hemorrhage in 23-gauge Vitrectomy: case report - Bingqian Liu; Yonghao Li; Tao Li; Ying Lin; Wei Ma; Lin Lu (BMC Ophthalmology, 2018)
Abstract Background Transscleral tunnel incisions are commonly made to avoid postoperative leakage in small gauge sutureless vitrectomy. We present an unreported intraoperative complication, tunnel incision related arterial hemorrhage from sclerotomy, in 23-gauge (23G) vitrectomy. Case presentation Two cases of intraocular arterial hemorrhage from superonasal sclerotomy were observed at the beginning of vitrectomy. The bleeding filled the vitreous cavity quickly and gushed out from the incision port after the involved supronasal cannula was removed. The active bleeding seemed not to stop spontaneously. We controlled the active bleeding by relocating the involved cannula, elevating the intraocular pressure and compressing the sclera wound. Post-operative intraocular hemorrhage from the sclerotomy was not found in any of the two cases. Conclusions We suggest that the bleeding was from injured ciliary artery when the incision crossed 3 or 9 o’clock accidently. Surgeons might avoid this complication by locating the superior incisions away from the horizontal axis, and should be aware the proper management.